MODERN EDUCATION SYSTEM - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article describes the role of modern education in the development of creative thinking, life skills, analytical skills and decision-making skills of students in educational institutions, as well as online education, which is considered the basis of modern education, and the advantages of independent education are described